Multi-person selection of the best wind turbine based on the multi-criteria integrated additive-multiplicative utility function - Bagočius, Vygantas; Zavadskas, Edmundas Kazimieras; Turskis, Zenonas (Journal of Civil Engineering and Management, 2014)
Energy generation and savings is a vital problem for the social and economic development of a modern world. The construction of wind farms is a challenge of crucial importance to Lithuania. Offshore wind farms are one of the possibilities of the multiple use of marine space. Wind energy industry has become the fastest growing renewable energy in the world. An offshore wind farm is considered one of the most promising sources of green energy towards meeting the EU targets for 2020 and 2050. They provide long-term green energy production. The major purpose of this study is the selection and ranking of the feasible location areas of wind farms and assessing the types of wind turbines in the Baltic Sea offshore area. Multi-criteria decision making methods represent a robust and flexible tool investigating and assessing possible discrete alternatives evaluated applying the aggregated WSM and WPM method namely WASPAS. The following criteria such as the nominal power of the wind turbine, max power generated in the area, the amount of energy per year generated in the area, investments and CO2 emissions have been taken into consideration.